VẤN ĐỀ NỮ QUYỀN TRONG TRUYỆN DÂN GIAN NGƯỜI VIỆT - Đặng, Quốc Minh Dương (Trường Đại học Đà Lạt, 2023)
Feminist issues are one of the interesting research areas attracting the attention of many researchers. In Vietnam, so far, there have been many journal articles on feminism in medieval, modern (1930-1945), and especially contemporary literature. In studying folklore – especially myths, legends, and fairy tales – we have found that a feminism-related consciousness was long ago taking shape. Through the construction of images of goddesses, groups of anonymous people recognized the contributions and merits of women. Through the world of folklore, these people showed their dreams for a just and equal society in which the freedom to love and the right to participate in social activities are re-established.